2022
DOI: 10.3389/fcimb.2022.933833
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Microbiome Profile of Diabetes and Periodontitis in a Chinese Population

Abstract: AimThere is a bidirectional association between diabetes and periodontitis. However, the effect of diabetes on the periodontitis salivary microbiota has not been elucidated. The aim of this study was to determine the effect of the presence of diabetes on the microbiota among Chinese patients with periodontitis.Materials and MethodsUnstimulated whole saliva samples were collected from the periodontitis with diabetes group (TC), chronic periodontitis group (CP), and periodontally healthy and systemically healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Prior studies consistently showed that oral H. parainfluenzae is decreased in PD. 28 , 29 The strain-level analysis allowed for the detection of biologically relevant strains that could play an essential role in the disease pathogenesis. However, whether the F3p strain affects the pathogenesis of PD remains debatable and more studies are needed to test the clinical relevance of salivary H. parainfluenzae F3p strains.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies consistently showed that oral H. parainfluenzae is decreased in PD. 28 , 29 The strain-level analysis allowed for the detection of biologically relevant strains that could play an essential role in the disease pathogenesis. However, whether the F3p strain affects the pathogenesis of PD remains debatable and more studies are needed to test the clinical relevance of salivary H. parainfluenzae F3p strains.…”
Section: Discussionmentioning
confidence: 99%
“…The beta diversity has been evaluated through principal coordinates analysis (PCoA) ordination of variance and compared using Bray-Curtis dissimilarity. Differential species among groups was explored with the linear discriminant analysis (LDA) effect size (LEfSe) method (Shi et al, 2021) and DESeq2 analysis (Lu et al, 2022). The microbiome phenotypes were predicted by BugBase (Ward et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Dickson et al revealed that Klebsiella pneumoniae overgrowth in the lung was strongly associated with ARDS . In addition, Klebsiella pneumoniae infection can influence both the gut microbiome and lung metabolome Jiang et al, 2022). After inoculation of mice with Klebsiella pneumoniae, the diversity and composition of the gut microbiota changed and contributed to lung microbiota dysbiosis within several hours (Jiang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Previous researches on a bi‐species biological model of Streptococcus and Veillonella found that the presence of Veillonella promotes Streptococcus pyogenes , Streptococcus gordonii , and Streptococcus salivarius (Chalmers et al, 2008; Mashima & Nakazawa, 2014). In addition, both Veillonella and Streptococcus also dominate the oral cavity of people with high sugar intake and cigarette smokers with depression and influence the balance of the oral microbiota and the host's health (Al Bataineh et al, 2022; Angarita‐Díaz et al, 2022; Lu et al, 2022). Network analysis also found a strong positive correlation between OS.Veillonella and CTSK.…”
Section: Discussionmentioning
confidence: 99%